A durabilidade da carroceria de um veículo de passeio simulada no laboratório - Samuel Elias Ferreira (2011)
Durability tests are part of the experimental development of a product aiming to submit it to the service conditions by evaluating their performance for a specified time. Over the years, these tests initially conducted on public roads have migrated to proving grounds speciallydesigned to reproduce certain service conditions and finally to the lab environment. Although it is an approximation of reality, the laboratory tests are developed for the validation of components and systems with the main advantages the time reduction, increased security and greater control of variables of influence. FIAT develops in Brazil accelerated durability tests on simulators since 1998 in parallel with road tests, in order to validate the design of body components. However in regions of the body as the attachment points of the exhaust system and engine mounts were found discrepancies between the results found on the road and the lab, which makes it impossible to complete validation of the body in the laboratory. The aim of this study was first analyze the vibration dynamics of the whole engine and exhaust relating them to the loads induced to the body and also verify the severity of an endurance test forthese regions using two road simulators. For the development were collected force, acceleration, temperature and strain data at specific points into the FIAT durability roads. These signals were editing, analyzed and further reproduced at the road simulators. One of the results was the recognition of the possibility of performing tests in order to validation theexhaust attachment points at lab. This study also discuss about the main efforts induced to the body vehicle that can be used for development of accelerated tests of its components and systems